Intellectual capital and company performance: the moderating effects of business strategy in the context of resource-based and knowledge-based theories / Amanuddin Shamsuddin - Shamsuddin, Amanuddin (Research Management Institute (RMI), 2017)
Malaysia aspired to transform its economy from an industralizing economy into a knowledge-based economy that is expected to help in achieving its Vision 2020.However, the new competitive landscape brought about by the shift into knowledge economy has presented companies with unprecedented strategic challenges for leveraging and making knowledge more productive as a competitive resource in a complex and unpredictable environment. Competitive success of businesses is depending more on strategic management of intellectual capital (IC) and less on the strategic allocation of physical and financial resources. The Resource-based Theory views that company resources such as IC are the key drivers of competitive advantages and vital to company financial performance. Meanwhile, the Knowledge based Theory further supports the view that unique sets of knowledge, and the distinctive ways in which knowledge is integrated and organised by the company, can generate capabilities that either create or support a company's competitive advantage. With this development, companies have begun to recognise the importance of IC. This study investigated IC within an organisational context by examining IC and how it impacted company's performance. The initial focus was on determining the main effect between IC and performance; followed by exploring the individual effects of the IC components on performance. The findings led to the development of an IC index for Malaysian companies. Thus, the study came up with a model named Malaysian Intellectual Capital Index (My-ICI). The Index is used to measure the IC management practices in Malaysian companies. Lastly, the study also examined the moderating effects of business strategy on the relationship between IC and performance. Data was obtained from a questionnaire survey from 178 Malaysian Public Listed companies from eight sectors. Results indicated that IC is a significant predictor to a company's selected performance measures (Return on Assets, Return onEquity and Earnings per Share) except for Price Earnings ratio. For the individual effects, results indicated that the highest interaction effects was on EPS which saw the interactions with all the four IC components. As for the ROA, only two components(innovation capital and customer capital) interact together to give some significant effects. Meanwhile, the results from the My-ICI indicated that majority (78%) of the Malaysian companies belongs into Integration stage, which means that they were practising IC management quite consistently across the companies with further improvement being made from time to time. In terms of IC and performance, the results indicated that all selected performance measures have significant effects on company's performance, with the exception of PE ratio. Lastly, the results indicated that business strategy, acted as moderating variable, played a significant role in predicting the performance of companies as far as IC is concern. The results from the multiple regression models proved that IC and business strategy are significant predictors for all selected performance measures, except for PE ratio. In summary, the results have shown that IC is an important organisational capability which should be considered as a strategic resource. IC provides an important link in explaining that successful companies are those that can manage and respond well to the new dynamics of company competition by being able to strike an optimal balance between their employment of tangible and intangible resources vis a vis IC.